A comprehensive accident investigation system for assisted driving vehicles: Addressing complexities in fault determination and responsibility allocation - Yanbin Hu; Wenhui Zhou (PLoS ONE, 2025)
China’s autonomous vehicle accidents, fault determination has grown increasingly complex due to the undefined legal status of autonomous driving systems. To assign responsibility accurately, it is crucial to consider the system’s autonomy and decision-making capabilities. Furthermore, the lack of specialized technical equipment and software for data collection, analysis, and processing hinders rapid and precise problem identification, impacting accident handling efficiency and accuracy. To address this, a tailored comprehensive accident investigation system for assisted driving vehicles has been developed. This system comprises subsystems for traffic accident boundary analysis, control action safety analysis, causal scene restoration, and investigation report output. It systematically extracts accident evidence, analyzes causes, traces hidden hazards, and determines responsibility. By integrating these subsystems, the system offers a structured and comprehensive framework for intelligent vehicle accident investigations, enhancing overall efficiency and clarity.